City resilience and recovery from COVID-19: The case of Macao. (May 2021) - McCartney, Glenn; Pinto, Jose; Liu, Matthew
Abstract: Due to COVID-19, Macao established a prolonged tourism lockdown for over half a year. With no COVID-19 cases for 3 months, the lockdown and resilient measures provided the ability to recover, becoming the first city globally to reopen travel borders to all of China. Using the case of Macao during a real-time pandemic crisis we develop a conceptual framework on economic resilience and tourism recovery. We propose for the first-time, destination vulnerabilities as a consequence of recovery and resilient actions. Contrary to government direction that Macao diversify beyond gaming revenues after COVID-19, our study affirms this is unlikely, as casino companies focus on recuperating revenue losses. Our theoretical assertions have wider implications as tourism cities globally look at COVID-19 exit strategies. The short-term resilient endeavors taken now by cities may have longer-term consequences on their 'reset' milieu. With the challenges of vaccination rollout, a COVID-19 exit will be prolonged further with continued economic and tourism recovery challenges for cities, giving greater significant the study's theoretical assertions. Highlights: Due to COVID-19, Macao became one of the first cities outside Mainland China to go into lockdown. The paper examines Macao's resilience throughout the half-year lockdown, with substantial government subsidies provided. After over 3 months COVID-19 free in Macao, the city reopened to all of China, signaling the city's recovery phase. With the 'how to' recover largely absent from the literature this paper developed a tourism resilience and recovery model. The paper showed consequences to recovery measures, an important reference to global cities looking to exit COVID-19.